2003
DOI: 10.1080/0034340032000128721
|View full text |Cite
|
Sign up to set email alerts
|

Changing Use of External Business Advice and Government Supports by SMEs in the 1990s

Abstract: BENNETT R. J. and ROBSON P. J. A. (2003) Changing use of external business advice and government supports by SMEs in the 1990s, Reg. Studies 37 , 795-811. This paper uses cross-sectional surveys of 1991 and 1997, a panel survey of firms surviving between 1991 and 1997 and comparison with a further cross-sectional survey in 1999, to compare the levels of use by SMEs of external business advice. The resource-based theory of the firm indicates that SMEs seek advice in order to increase their competitive capacity.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
122
0
15

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(143 citation statements)
references
References 25 publications
5
122
0
15
Order By: Relevance
“…There has, however, been considerable research exploring the impact of advisory networks on small and medium-sized enterprises (SMEs) as a whole. This research has found that SMEs make greater use of such advice than do large businesses (Forth et al 2006, p. x), with SME use of external advice on personnel and recruitment issues having more than doubled in the 1990s (Bennett and Robson 2003). This is perhaps unsurprising given the lack of HR expertise within such businesses and the extent to which external advice can reduce the search costs associated with finding solutions to employment-related problems.…”
Section: Access To Expertisementioning
confidence: 72%
See 1 more Smart Citation
“…There has, however, been considerable research exploring the impact of advisory networks on small and medium-sized enterprises (SMEs) as a whole. This research has found that SMEs make greater use of such advice than do large businesses (Forth et al 2006, p. x), with SME use of external advice on personnel and recruitment issues having more than doubled in the 1990s (Bennett and Robson 2003). This is perhaps unsurprising given the lack of HR expertise within such businesses and the extent to which external advice can reduce the search costs associated with finding solutions to employment-related problems.…”
Section: Access To Expertisementioning
confidence: 72%
“…For example, Erickson and Jacoby (2003) and Hoque and Bacon (2006) find that SMEs that are members of multiple business advisory networks are more likely to train their employees than are non-members of such networks. However, Bennett and Robson (2003) argue that the use of external advice increases once businesses grow beyond the small business size threshold, as business growth requires owner-managers to increase employee training and improve recruitment processes rather than retain their own personal approach to management (Curran and Government-sponsored initiatives such as Investors in People (IiP) might provide another source of external expertise for small businesses. IiP offers a best practice blueprint for small businesses to work towards, hence one might expect HPWPs to have been more widely adopted in small businesses that have secured IiP recognition (Goss et al 1994).…”
Section: Access To Expertisementioning
confidence: 99%
“…The RBV indicated that the use of external services interacts with the size and age of the firm (Bennett and Robson, 2003). Empirical studies indicate that utilisation of advisory services by SMEs is positively related to firm size and firm age (Bennett and Robson, 1999;Dyer and Ross, 2008).…”
Section: Control Variablesmentioning
confidence: 99%
“…RBV describes the use of external services interrelates with the size and age of the company (Bennett & Robson, 2003). Empirical studies indicated that the use of external advisory services by SMEs is significantly positively related to the size and age of the firm (Dyer & Ross, 2008;Bennett & Robson, 1999).…”
Section: Control Variablesmentioning
confidence: 99%